Penguatan Positif sebagai Upaya Menumbuhkan Perilaku Disiplin pada Siswa Sekolah Dasar - Haqq, Yussidah Azmiyatul (Faculty of Psychology, University of Muhammadiyah Malang, Indonesia, 2019)
Discipline can be defined as an indication of one’s behavior, that occurs in a regulations of an institute, either written or unwritten. An individual with a self-discipline behavior is likely to obey the rules and regulation and is easier ro be ruled than those who don’t. There are two ways to get self-discipline for students. Punishment or positive reinforcement. However, positive reinforcement is more reliable because it will give stronger effect to change one’s behavior. This research is using a Single Case kind of research with a Quasi Experiment design. This experiment uses guide observations and interviews. The subject in the experiment is a couple of male students who don’t have self-discipline. To determine the subject is to use Purposive Sampling. The result of the research is that there is a behaviour change from not having a self-discipline to having a self-discipline after given a treatment. This shows that Positive reinforcement has better effect towards student’s self-discipline.